Personalized Learning Through Artificial Intelligence: A Literature Review - Shoffan Fatkhulloh; A. Afrinaramadhani Hatta (Sains Global Institut, Indonesia, 2026)
Artificial intelligence (AI) offers pedagogical solutions to address the global learning crisis, but the literature specifically examines its application to learning personalization is limited. This study aims to examine how AI technology can personalize students' learning experiences and why AI needs to be mastered as an educational productivity tool, not avoided. The method used is a literature review with a search through Google Scholar using the combined keywords